Wage dispersion and decentralization of wage bargaining - Christian M. Dahl; Daniel le Maire; Jakob R. Munch (Institute for the Study of Labor (IZA), 2011)
This paper studies how decentralization of wage bargaining from sector to firm-level influences wage levels and wage dispersion. We use detailed panel data covering a period of decentralization in the Danish labor market. The decentralization process provides variation in the individual worker's wage-setting system that facilitates identification of the effects of decentralization. We find a wage premium associated with firm-level bargaining relative to sector-level bargaining, and that the return to skills is higher under the more decentralized wage-setting systems. Using quantile regression, we also find that wages are more dispersed under firm-level bargaining compared to more centralized wage-setting systems.
urn:nbn:de:101:1-201201103073
Keywords: J31; J51; C23; 330; wage bargaining; decentralization; wage dispersion; Lohnverhandlungen; Lohnniveau; Lohnstruktur; Lohndrift; Panel; Dänemark